Birth rates among female cancer survivors1: A population‐based cohort study in Sweden. Issue 10 (21st February 2013) - Hartman, Mikael; Liu, Jenny; Czene, Kamila; Miao, Hui; Chia, Kee Seng; Salim, Agus; Verkooijen, Helena M.
Abstract: BACKGROUND: More women of fertile age are long‐term survivors of cancer. However, population‐based data on birth rates of female cancer survivors are rare. METHODS: A total of 42, 691 women ≤ 45 years with a history of cancer were identified from the Swedish Multi‐Generation Register and the Swedish Cancer Register, for whom relative birth rates were calculated as compared to the background population, ie, standardized birth ratios (SBRs). Independent factors associated with reduced birth rates among cancer survivors were estimated using Poisson modeling. RESULTS: Compared to the background population, cancer survivors were 27% less likely to give birth (SBR = 0.73, 95% confidence interval [CI] = 0.72‐0.75). Large difference in SBRs existed by cancer site, with high SBRs for survivors of melanoma skin, thoracic, head and neck, and thyroid cancers, and low SBRs for reproductive, breast, brain and eye, and hematopoietic cancer survivors. Parity status at diagnosis affected fertility: women who already had a child at the time of diagnosis were less likely to give birth (SBR = 0.50, 95% CI = 0.48‐0.53) than were nulliparous women (SBR = 0.87, 95% CI = 0.85‐0.90). Multivariate analysis showed that cancer site (reproductive organs), age at onset of cancer (< 12 years), and parity status were all significant and independent predictors of a reduced probability of giving birth after diagnosis. CONCLUSIONS: Cancer survivors are less likely to give birth compared with the background population. Large variations in the likelihood to give birth after diagnosis were seen according to age at onset, cancer site, and parity status at diagnosis. Cancer 2013. © 2013 American Cancer Society. Abstract : Female cancer survivors are less likely to give birth as compared to the background population. This study suggests that large variations in the birth patterns among female cancer survivors were attributed to parity status at diagnosis, age at onset, and cancer site.